A Case of Erythropoietic Protoporphyria. Issue 3 (1st July 2016) - Lindsey, Kathryn; Burch, Micah; Krause, John R.
Abstract : A 53-year-old Texas rancher developed a blistering skin rash that was sensitive to exposure to sunlight. He was referred to hematology with a presumptive diagnosis of porphyria. His peripheral blood counts were within normal limits, and a bone marrow examination revealed erythroid dyspoiesis and ringed sideroblasts. Serum, plasma, and erythrocyte protoporphyrin levels were elevated, the findings of which are consistent with a diagnosis of erythropoietic protoporphyria. This paper discusses the diagnosis and etiology of the porphyrias.